2022
DOI: 10.3389/fphar.2022.828627
|View full text |Cite
|
Sign up to set email alerts
|

Roles of MicroRNA-21 in Skin Wound Healing: A Comprehensive Review

Abstract: MicroRNA-21 (miR-21), one of the early mammalian miRNAs identified, has been detected to be upregulated in multiple biological processes. Increasing evidence has demonstrated the potential values of miR-21 in cutaneous damage and skin wound healing, but lack of a review article to summarize the current evidence on this issue. Based on this review, relevant studies demonstrated that miR-21 played an essential role in wound healing by constituting a complex network with its targeted genes (i.e., PTEN, RECK. SPRY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 110 publications
(143 reference statements)
0
17
0
Order By: Relevance
“…Predominantly, miR-21 can control various functions of fibroblasts, such as extracellular matrix production, angiogenesis, and inflammation control. This can be particularly important during wound healing and cancer progression [ 30 ]. This striking similarity is not surprising, because wound healing and the cancer microenvironment exhibit many similarities at the cellular and molecular levels [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Predominantly, miR-21 can control various functions of fibroblasts, such as extracellular matrix production, angiogenesis, and inflammation control. This can be particularly important during wound healing and cancer progression [ 30 ]. This striking similarity is not surprising, because wound healing and the cancer microenvironment exhibit many similarities at the cellular and molecular levels [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The major advancements in wound healing include stem cell transplantation, exploiting tissue engineering, implementation of exosomes, and the use of miRNAs in tissue regeneration . miRNA-21-5p has been reported to be a crucial regulator of fibroblast differentiation and angiogenesis, the resolution of inflammation, collagen synthesis, re-epithelialization, cell migration and invasion, and apoptosis and improves both the rate and quality of wound healing via the BMP, Smad7-Smad2/3-elastin, TGF-β, MAPK/ERK, PI3K/Akt, and Wnt/β-catenin/MMP-7 signaling pathways. Accordingly, we loaded YARA-miRNA-21-5p into UC-MSC-derived exosomes and subsequently investigated if the loaded exosomes had positive effects on one or more aspects of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed a simple peptide-based technology for miRNA loading into exosomes secreted from different mammalian cells, including MSCs, without genetic modification of the parent cells. Here, miRNA-21-5p, a mammalian microRNA known to regulate fibroblast differentiation, angiogenesis, and apoptosis, was selected to be the model miRNA. To determine the functionality of our loading technology, we then assessed the impact of the loaded exosomes in wound healing assays.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies are necessary to determine whether a compensatory upregulation observed in BCL11B expression in absence of BCL11A is a contributor towards the accelerated healing phenotype. Furthermore, noncoding RNAs such as microRNAs (miRNA) and long noncoding RNAs (lncRNA) have received significant attention recently, owing to their rapidly emerging role in modulating nearly every stage of a healing cascade [75][76][77][78][79]. The characterization of expression of noncoding RNAs in the Bcl11a ep−/− mutant skin might provide additional cues about its mechanistic role in facilitating healing.…”
Section: Discussionmentioning
confidence: 99%